From the Competence Model of a Specialist Engineer to STEAM Education, or … Going Ahead to the Past? - N. G. Bagdasaryan; R. M. Petruneva; V. D. Vasilyeva (Высшее образование в России)
Cognitive and value dissonances of the modern world, as well as the shifting balance in the “Technology-nature-society-man” system cause the need to rethink key development strategies, determine the guidelines that education should be guided by in order to be able to respond to the growing global challenges of modernity. The special acuteness of the modern formulation of this problem is due to the new format of the geopolitical life of the Russian Federation and the associated restructuring of many social institutions of the country, in particular, science and education.The article raises the question of the leading paradigm of domestic engineering education, considered in the prism of a specialist-engineer model that meets the requirements of the modern stage of society.Education standards have changed dramatically and repeatedly in their target characteristics over the past twenty years. The article considers the features of the competence model of specialist presented in the modern version of the Federal State Educational Standards of higher education (FSES HE). It is shown that the existing version of FSES does not fully meet the requirements for specialists in the modern world. In addition to highly professional knowledge and skills, future engineers need contextual, meta-professional and soft knowledge and skills for life and successful professional activity.World practice shows that one of the promising areas of training engineers is a project-oriented approach, which emphasizes the practical orientation of higher education. The authors have shown that the recognized international standards of engineering education in the fields of technology, natural and applied sciences (CDIO, STEM education) basically coincide with the world-known and repeatedly tested “Russian method of training engineers”, integrating broad fundamental education in the field of natural sciences and humanities and technological practice at advanced innovative enterprises. This experience which has already given the world great engineers and adapted at the same time to the modern technological capabilities of its transmission can become a fulcrum in a transitive world.